2017
DOI: 10.3892/mmr.2017.8227
|View full text |Cite
|
Sign up to set email alerts
|

miR‑96 inhibits EMT by targeting AEG‑1 in glioblastoma cancer cells

Abstract: The induction of epithelial to mesenchymal transition (EMT) is important for carcinogenesis and cancer progression. Previous studies have estimated that microRNA (miRNA/miR) expression is associated with EMT via the regulation of the expression of target genes. miR-96 has been reported to exhibit a correlation with the EMT process. However, the functional role of miR-96 and its mechanism in glioblastoma multiforme (GBM) remains to be completely elucidated. The objective of the present study was to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Chang and Lai (17) demonstrated that miR-96 may be used as a biomarker of ischemia-reperfusion injury in skin tissues. A recent study observed that miR-96 may represent a potential anticancer therapeutic target to treat glioblastoma (35). miR-96 was previously observed to serve as an oncosuppressor gene by targeting NUAK family kinase 1 in pancreatic cancer (36).…”
Section: Discussionmentioning
confidence: 99%
“…Chang and Lai (17) demonstrated that miR-96 may be used as a biomarker of ischemia-reperfusion injury in skin tissues. A recent study observed that miR-96 may represent a potential anticancer therapeutic target to treat glioblastoma (35). miR-96 was previously observed to serve as an oncosuppressor gene by targeting NUAK family kinase 1 in pancreatic cancer (36).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, miR-140, miR-101-3p, miR-577, miR-96, and miR211 suppressed GBM mesenchymal properties by targeting cathepsin B, TRIM44, Rab25, AEG-1, and HMGA2, respectively. [77][78][79][80][81] On the other hand, aberrant expression of miR-10b is associated with grade IV gliomas as well as PMT. [82] Agomir (a miRNA mimic) of miR-10b injection enhances tumor growth in vivo, while miR-10b mimics induces a significant morphological change of GBM cells from pebble shape to the long fusiform shape, a feature of PMT.…”
Section: Epigenetic Regulationmentioning
confidence: 99%
“…Overexpression of AEG1 has been documented to be involved in many tumors' biological processes, including tumor proliferation, metastasis, EMT. [12][13][14][15] To evaluate the possibility that AEG1 is important for HCC, we examined AEG1 expression in corresponding noncancerous tissues and HCC using Gene Expression Profiling Interactive Analysis (GEPIA) website based on TCGA database. 16 Notably, AEG1 expression in HCC samples was significantly higher compared to normal samples ( Figure 3A).…”
Section: Aeg1 Is Identified As a Target Of Mir-885-5pmentioning
confidence: 99%